Penggunaan Zoom Meeting pada Pembelajaran RADEC terhadap Kemampuan Berpikir Kritis IPA - Najah, Naylan; Sujana, Atep; Isrokatun, Isrokatun (Jurnal Pena Ilmiah, 2021)
The goal of this study is to see how RADEC learning is implemented via zoom meetings on heat transfer subject, as well as to see how students' critical thinking skills improve after learning. In this study, three markers were used to increase students' critical thinking skills: offering a straightforward explanation of heat transfer, solving heat transfer questions, and closing the topic. The participants in this study were one teacher who used a zoom meeting to educate using the RADEC model and six grade 6 students from SD Islam Al-Falah 1 Pagi. Observation, documentation, exams, and questionnaires were utilized to collect data. Students' critical thinking skills are assessed by tests, and student answers are assessed through questionnaires after learning. According to the findings of this study, the use of zoom meetings to apply RADEC learning is effective and has a favorable impact on students' critical thinking skills.